AB1099 Obesity and fibromyalgia: Relationship between body mass index and severity of the symptoms. (23rd January 2014) - Castro, S.; Poveda, M.J.; Fontova, R.; Castel, A.; Qanneta, R.; Montull, S.; Periñán, R.; Miralles, I.; Aragonés, N.; Salvat, I.; Cascόn, R.; Monterde, S.; et al.
Abstract : Background: Fibromyalgia (FM) is a prevalent musculoskeletal chronic pain condition. Obesity is frequent in patients with FM. Several studies suggests that body mass index (BMI) is related with pain intensity and quality of life. Objectives: 1) To determine the prevalence of obesity in a sample of women with FM. 2) To determine the relationship between obesity and the following variables: pain intensity, functionality, psychological distress, quality of life, and sleep problems. Methods: 152 women with FM according to the American College of Rheumatology criteria who participated in a multidisciplinary treatment. Patients were assessed before treatment, after treatment, and at 3-6-12 month follow-up. Measures: Body Mass Index (BMI), pain intensity (Numeric Rating Scale), functionality (FIQ), psychological distress (HADS), quality of life (COOP-WONCA), and sleep problems (Medical Outcome Study: MOS). Patients were classified according their BMI: normal weight (BMI <25), overweight (BMI 25.0-29.9), obesity (BMI ≥30). Results: The 30.9% (N=47) of the patients were normal weight, the 40.1% (N=61) overweight, and the remaining 28.9% (N=44) obese. Groups were homogeneous regarding to age. ANOVA analysis, with Bonferroni correction, showed no differences between groups in the assessed measures, except in pain intensity. Patients with obesity had more pain than patients with overweight (p<.01). Conclusions: 1) As already stated in previous studies, obesity was a frequent comorbid condition in patients with FM. 2) Patients with obesity had more pain than overweight patients. 3) Weight didn't determine differences in the other studied variables. Supported by the Foundation Maratό Grant Number 070910 Disclosure of Interest: None Declared